HUBUNGAN KARAKTERISTIK TERHADAP PENGETAHUAN DAN SIKAP KADER KESEHATAN TENTANG PENTINGNYA DATA DI BUKU KIA - Yudhy Dharmawan (LPPM Universitas Pekalongan, 2015)
Infant Mortality in Indonesia still high . It is could have been avoided with good management of MCH services. To achieve good management activities, it is necessary availability data from surveillance activities in the community. The data is sourced in the MCH handbook. Cadre very important role in the completeness and validity of data captured in the MCH handbook. Knowledge and attitudes cadres determine the data recording in the MCH handbook. Therefore it is important to know what are the factors that influence the knowledge and attitudes about the importance of data Kader KIA. The research method used survey approach by looking at the relationship between age, education and length of employment with the attitude and knowledge of cadres. Results showed characteristic Cadres of the age, including adulthood, with most respondents education is the primary level. length of employment been a cadre mean is 8.06 years. Most of the knowledge and attitudes of the respondents about the importance of data MCH very good ,. There is a significant and positive relationship between education with the knowledge and attitudes about the importance of data MCH. There is a significant relationship between age and in contrast with the attitude of the cadres of the importance of data MCH. There is no relationship between the old cadre with knowledge and attitudes about the importance of data KIA cadre. It is advisable to pay attention to the education cadre recruitment. Keywords: Health Cadre, Data, Book KIA